Ambrein: a minor, but common constituent of mammalian faeces?. Issue 22 (17th November 2021) - Rowland, Steven J.; Sutton, Paul A.; von der Lühe, Barbara; Volkman, John K.; Vane, Christopher H.; Ingram, Simon N.; Dunn, Charlotte; Claridge, Diane
Abstract: For nearly 200 years, the only natural source of the alcohol ambrein has been coproliths produced in about 1% of sperm whales and in related jetsam. However, the finding of ambrein in adipocere/faeces of human corpses, led us to hypothesise that ambrein might occur in the faeces of other mammals. Herein, we used a recently developed gas chromatography-mass spectrometry method, with suitable derivatisation of the hindered hydroxy group of ambrein, to screen a number of extracts of mammalian faeces. Minor proportions of ambrein were detected in digested human sewage sludge and in the dung of elephant, domestic cattle, giraffe and buffalo. Whether ambrein formation in the terrestrial species is associated with coprolith formation, is unknown, but solid deposits known as enteroliths and fecaliths occur in humans and some domestic animals. Abstract : UF0001